Biallelic variants in UBA5 reveal that disruption of the UFM1 cascade can result in early-onset encephalopathy - Colin, Estelle; Assmann, Birgit; Christ, Stine; Hoffmann, Georg F. (The American journal of human genetics, 2016)
Via whole-exome sequencing, we identified rare autosomal-recessive variants in UBA5 in five children from four unrelated families affected with a similar pattern of severe intellectual deficiency, microcephaly, movement disorders, and/or early-onset intractable epilepsy. UBA5 encodes the E1-activating enzyme of ubiquitin-fold modifier 1 (UFM1), a recently identified ubiquitin-like protein. Biochemical studies of mutant UBA5 proteins and studies in fibroblasts from affected individuals revealed that UBA5 mutations impair the process of ufmylation, resulting in an abnormal endoplasmic reticulum structure. In Caenorhabditis elegans, knockout of uba-5 and of human orthologous genes in the UFM1 cascade alter cholinergic, but not glutamatergic, neurotransmission. In addition, uba5 silencing in zebrafish decreased motility while inducing abnormal movements suggestive of seizures. These clinical, biochemical, and experimental findings support our finding of UBA5 mutations as a pathophysiological cause for early-onset encephalopathies due to abnormal protein ufmylation.
Gesehen am 02.02.2018